Newborns are sensitive to multiple cues for word segmentation in continuous speech. Issue 4 (20th February 2019) - Fló, Ana; Brusini, Perrine; Macagno, Francesco; Nespor, Marina; Mehler, Jacques; Ferry, Alissa L.
Abstract: Before infants can learn words, they must identify those words in continuous speech. Yet, the speech signal lacks obvious boundary markers, which poses a potential problem for language acquisition (Swingley, Philos Trans R Soc Lond. Series B, Biol Sci 364 (1536), 3617–3632, 2009). By the middle of the first year, infants seem to have solved this problem (Bergelson & Swingley, Proc Natl Acad Sci 109 (9), 3253–3258, 2012; Jusczyk & Aslin, Cogn Psychol 29, 1–23, 1995), but it is unknown if segmentation abilities are present from birth, or if they only emerge after sufficient language exposure and/or brain maturation. Here, in two independent experiments, we looked at two cues known to be crucial for the segmentation of human speech: the computation of statistical co‐occurrences between syllables and the use of the language's prosody. After a brief familiarization of about 3 min with continuous speech, using functional near‐infrared spectroscopy, neonates showed differential brain responses on a recognition test to words that violated either the statistical (Experiment 1) or prosodic (Experiment 2) boundaries of the familiarization, compared to words that conformed to those boundaries. Importantly, word recognition in Experiment 2 occurred even in the absence of prosodic information at test, meaning that newborns encoded the phonological content independently of its prosody. These data indicate that humans are born with operational language processing and memory capacities and can use at least two types of cues to segment otherwise continuous speech, a key first step in language acquisition. Abstract : After we familiarized newborns with about three minutes of continuous speech containing either distributional or prosodic cues, we observed a differential response for sequences that adhered to the boundaries compared to sequences that did not.